Aluminium-based Composite Materials in Construction of Transport Means - Miloš, Katica; Jurić, Ivica; Škorput, Pero (Promet - Traffic&Transportation, 2012)
The implementation of the achievements in material science both through history as well as today, is directly indicated in the improvement of the efficiency of transport means which then results in the improvement of the technology of traffic and transport. Today’s requirements in the area of engineering materials intended for the construction of transport means impose reduction of mass as one of the fundamental criterion. Consideration of the technical and technological societies have been oriented towards light materials and the possibilities of their modification in order to substitute the past traditional heavy monoliths such as iron, steel, copper, etc. The potential has been recognised in the aluminium-based materials. Aluminium and its versions have been already widely used in automotive industry; however, their utility spectrum still avoids the tribologically sensitive purposes. This paper is focused on the possibility of producing such a material. Ceramic particles Al2O3 have been integrated into soft aluminium, various particle sizes and share, by powder metallurgy techniques. The mechanical properties of materials have been studied in dependence on the share, size of particles, type of Al/Al2O3, as well as the graphite addition. Al/Al2O3 composites have been produced without any problems and have shown satisfactory mechanical properties. KEYWORDS: reduction of transport means mass, aluminium-based composites, Al/Al2O3 composites